KONSEP KESELAMATAN DAN APLIKASINYA DALAM PENGINJILAN - herni wati hia (FILADELFIA: Jurnal Teologi dan Pendidikan Kristen, 2022)
This paper discusses the concept of salvation and its application in evangelism. The method used is library research with Bible sources, books, and other sources related to salvation. Salvation is a gift from God to sinners. Salvation is provided by God so that humans cannot die but have eternal life with Him.Keywords: Salvation, God, Evangelism.